Protective pathways against adolescent cyberbullying: democratic parenting, online risk behavior, and the mediating role of digital literacy - Maria Ulfa Ulfa; Ria Safaria Sadif; Amanda Putri Amalia; Hartati S Mey Wally (Jurnal Konseling dan Pendidikan, 2026)
Adolescents’ engagement in digital spaces has increased exposure to cyberbullying, while protective mechanisms linking family context, online risk behavior, and digital competence remain insufficiently explained. This study examined protective pathways against adolescent cyberbullying by testing the effects of democratic parenting and online risk behavior on cyberbullying vulnerability, with digital literacy as a mediator. A cross-sectional survey was conducted among 200 senior high school students from SMAN 1 Baubau, SMAN 2 Baubau, and SMAN 3 Baubau, selected through stratified purposive sampling. Data were analyzed using PLS-SEM with SmartPLS 3.0. The measurement model met validity and reliability criteria. The structural model explained 51.6% of the variance in digital literacy and 59.4% in cyberbullying vulnerability. Democratic parenting positively predicted digital literacy (β = 0.586, p < .001) and negatively predicted cyberbullying vulnerability (β = -0.251, p < .001). Online risk behavior negatively predicted digital literacy (β = -0.248, p < .001) and positively predicted cyberbullying vulnerability (β = 0.423, p < .001). Digital literacy negatively predicted cyberbullying vulnerability (β = -0.269, p < .001) and mediated both relationships. Findings imply that cyberbullying prevention should strengthen democratic parenting, reduce online risk behavior, and develop digital literacy through school counseling and family-based interventions.